2017
DOI: 10.1053/j.gastro.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Update: The Use of Per-Oral Endoscopic Myotomy in Achalasia: Expert Review and Best Practice Advice From the AGA Institute

Abstract: The purpose of this review is to describe a place for per-oral endoscopic myotomy (POEM) among the currently available robust treatments for achalasia. The recommendations outlined in this review are based on expert opinion and on relevant publications from PubMed and EMbase. The Clinical Practice Updates Committee of the American Gastroenterological Association proposes the following recommendations: 1) in determining the need for achalasia therapy, patient-specific parameters (Chicago Classification subtype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 57 publications
1
93
0
2
Order By: Relevance
“…Retrospective analyses of randomized [30] and non-randomized treatment series [31, 32] have, however, confirmed the original observation of differential response rates. Furthermore, with the recognition of obstructive physiology at the EGJ or distal esophagus being important foci of treatment, several disease entities beyond classical achalasia are now being rendered treatments formerly reserved for achalasia [2]. This is particularly relevant with the widespread adoption of the POEM procedure.…”
Section: A New Perspective On Management: Phenotype-directed Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective analyses of randomized [30] and non-randomized treatment series [31, 32] have, however, confirmed the original observation of differential response rates. Furthermore, with the recognition of obstructive physiology at the EGJ or distal esophagus being important foci of treatment, several disease entities beyond classical achalasia are now being rendered treatments formerly reserved for achalasia [2]. This is particularly relevant with the widespread adoption of the POEM procedure.…”
Section: A New Perspective On Management: Phenotype-directed Treatmentmentioning
confidence: 99%
“…Among these the most extensive literature, recently summarized by Pandolfino, has compared PD to LHM and concluded that both are highly efficacious, albeit best when done in expert hands [39]. On the other hand, uncontrolled outcome data have been very promising comparing POEM with LHM [2, 40]. True, POEM is relatively new, but with the pioneering Japanese center recently summarizing their experience gleaned from their first 1000 POEM procedures [41], one can hardly classify it as ‘experimental’.…”
Section: A New Perspective On Management: Phenotype-directed Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Achalasia is defined by its typical pattern at manometry according to the Chicago Classification, characterized primarily by aperistalsis of the esophageal body and incomplete relaxation of the LES. Different types of achalasia exist which affect the prognosis after treatment . Typically, achalasia is subtyped: subtype I is characterized by absent peristalsis without abnormal pressure; subtype II by absent peristalsis with abnormal pan‐esophageal high‐pressure patterns; and subtype III by absent peristalsis with distal esophageal spastic contractions .…”
Section: Definition Of Achalasiamentioning
confidence: 99%
“…Heller myotomy and pneumatic balloon dilation used to be the treatment of choice. However, the less invasive myotomy conducted by per‐oral endoscopic myotomy (POEM) is nowadays the preferred treatment for achalasia, and especially recommended as the choice for type III achalasia . These treatments reduce the barrier that the normal sphincter provides to gastroesophageal reflux, allowing the flow of gastric contents into the esophagus, resulting in esophageal inflammation.…”
Section: Course and Treatmentmentioning
confidence: 99%